Reduction in Jail Emergency Department Visits and Closure After Implementation of On-Site Urgent Care. (January 2017) - Eiting, Erick; Korn, Carrie S.; Wilkes, Erin; Ault, Glenn; Henderson, Sean O.
This descriptive study evaluates the impact of implementation of full service on-site urgent care services at the Los Angeles County Jail (LACJ) by examining the number of patients seen at the referral hospital, Los Angeles County + University of Southern California Medical Center (LAC+USC), and the number of hours that the referral hospital was closed to transfers in the periods before and after the development of the LACJ Urgent Care. The appropriate utilization of public resources is a critical priority for an overburdened county medical health care system. Implementing on-site urgent care staffed by emergency physicians led to reductions in the average number of patients transferred to LAC+USC, the average number of monthly closure hours, and the average days per month when closure to transfer occurred, and a cost savings of some $2 million, primarily in personnel costs.